The mandibular molar pit-tubercle (MMPT) dental nonmetric trait: Comprehensive analysis of a large sample - Marado, Luís Miguel (2019)
Dental nonmetric traits are quasicontinous variables, mostly of genetic origin. Thus, sets of such traits allow biological distance estimation between samples. Mandibular molar pit-tubercle (MMPT) is a buccal trait defined by Weets (2009) in Irish samples. This study aims to analyze (a) trait frequencies, (b) grade definitions, (c) intraobserver error, (d) sexual dimorphism, (e) asymmetry, and (f) trait associations for MMPT in a Portuguese sample. The first (LM1), second (LM2) and third (LM3) lower molars of 600 identified individuals from the Coimbra collections were scored for MMPT in three scoring sessions. Intraobserver error, bilateral asymmetry and trait correlations were tested using Kendall's τ-b, while sexual dimorphism was verified using Pearson's χ2. Frequencies (LM1: 2.1%; LM2: 3.5%; LM3: 30.3%) were similar to previous reports. However, a new free apex cusp form (grade 3+) was detected. Considering three scoring sessions, intraobserver precision was above 85%, and correlation coefficients between observations were positive and moderate to very strong (0.291<τ-b<0.835). Intrasample variation was low, since only LM3 showed sexual dimorphism (female: 30.2%; males: 16.2%; χ2=15.512; p<0.001; df=1; n=556) and large asymmetry (27.1%). There were no strong (τ-b>0.3) intertrait associations involving MMPT. MMPT shows low trait presence, sexual dimorphism and asymmetry in stable teeth (LM1 and LM2). Intraobserver precision is high, so scoring should be reliable, although a plaque and better threshold grade definition is needed. After further research on non-European samples, MMPT can be useful in biodistance research.